Regulasi Peran Maternal Perempuan Studi Analisis atas Novel Beloved Karya Toni Morrison - Yuniar Fatmasari (UIN Raden Mas Said Surakarta, 2016)
AbstractBasically, the body of the black woman slaves have experienced an immensely oppression whether from the economic, politic, and ideological dimensions; nevertheless, it is the ideological strategy which is believed in contributing the biggest and furthest effect so that the oppression still exists even the slavery has been abolished. During the slavery, the black woman slaves are forced to give birth as many as possible for the profit of the master. This shows that there is a control over the womb of the black woman slave. One of the strategies that the writer wants to convey in this article is the regulation on the maternal role of the black woman slaver. The individual maternal role is considered as a good strategy to conquer the body of the black woman slave so that they and the post-slavery black women are placing a disadvantage position in the social structure. Racism, sexism, class, and gender issues are assumed as the causal factors of this kind of social inequity.Keywords: individual maternal role, communal maternal role AbstrakPada dasarnya, tubuh budak perempuan kulit hitam telah mengalami opresi secara besar-besaran baik dari dimensi ekonomi, politik dan ideologi; namun demikian, strategi ideologi-lah yang dipercaya memberikan efek paling besar dan dalam sehingga opresi tetap ada bahkan meski perbudakan itu sendiri telah ditiadakan. Selama perbudakan,budak perempuan kulit hitam dipaksa melahirkan anak sebanyak mungkin untuk kepentingan profit sang majikan dan hal tersebut menunjukkan adanya kontrol terhadap rahim budak perempuan kulit hitam. Salah satu strategi yang penulis ingin kemukakan di dalam artikel ini adalah regulasi terhadap peran maternal budak perempuan kulit hitam. Peran maternal individu dianggap strategis untuk menguasai tubuh perempuan kulit hitam sehingga budak perempuan kulit hitam dan perempuan kulit hitam pasca perbudakan menempati posisi yang tidak menguntungkan di dalam struktur sosial.Wacana rasisme, seksisme, kelas dan gender diasumsikan menjadi faktor penyebab ketimpangan sosial semacam ini.Kata kunci: peran maternal individu, peran maternal komunal